Factors Influencing the Development of Public Universities’ Personnel Specialists - Nguyen Thi, Xuan Loc (Technium Education and Humanities, 2023)
Developing public universities’ personnel specialists is essential in the current period to enhance the quality of higher education human resources and meet the requirements of the fundamental and comprehensive reform of higher education. This article figures out the factors influencing the development of public universities’ personnel specialists, including globalization and internationalization trend, the development of the knowledge-based economy, and the fourth industrial revolution; the fundamental and comprehensive reform of higher education; State’s guidelines and policies; working environment; perception of public universities’ personnel specialists of their roles and positions in the universities; competencies of public universities’ personnel specialists; administrators for the development of public universities’ personnel specialists.